Stroke Correlates in Chagasic and Non-Chagasic Cardiomyopathies - da Matta, José Alberto Martins (Public Library of Science, 2012)
BACKGROUND: Aging and migration have brought changes to the epidemiology and stroke has been shown to be independently associated with Chagas disease. We studied stroke correlates in cardiomyopathy patients with focus on the chagasic etiology. METHODOLOGY/PRINCIPAL FINDINGS: We performed a cross-sectional review of medical records of 790 patients with a cardiomyopathy. Patients with chagasic (329) and non-chagasic (461) cardiomyopathies were compared. There were 108 stroke cases, significantly more frequent in the Chagas group (17.3% versus 11.1%; p<0.01). Chagasic etiology (odds ratio [OR], 1.79), pacemaker (OR, 2.49), atrial fibrillation (OR, 3.03) and coronary artery disease (OR, 1.92) were stroke predictors in a multivariable analysis of the entire cohort. In a second step, the population was split into those with or without a Chagas-related cardiomyopathy. Univariable post-stratification stroke predictors in the Chagas cohort were pacemaker (OR, 2.73), and coronary artery disease (CAD) (OR, 2.58); while atrial fibrillation (OR, 2.98), age over 55 (OR, 2.92), hypertension (OR, 2.62) and coronary artery disease (OR, 1.94) did so in the non-Chagas cohort. Chagasic stroke patients presented a very high frequency of individuals without any vascular risk factors (40.4%; OR, 4.8). In a post-stratification logistic regression model, stroke remained associated with pacemaker (OR, 2.72) and coronary artery disease (OR, 2.60) in 322 chagasic patients, and with age over 55 (OR, 2.38), atrial fibrillation (OR 3.25) and hypertension (OR 2.12; p = 0.052) in 444 non-chagasic patients. CONCLUSIONS/SIGNIFICANCE: Chagas cardiomyopathy presented both a higher frequency of stroke and an independent association with it. There was a high frequency of strokes without any vascular risk factors in the Chagas as opposed to the non-Chagas cohort. Pacemaker rhythm and CAD were independently associated with stroke in the Chagas group while age over 55 years, hypertension and atrial fibrillation did so in the non-Chagas cardiomyopathies.